Puzzle-shaped rib shear connectors subjected to combined shear and tension. (June 2018) - Classen, Martin; Herbrand, Martin; Adam, Viviane; Kueres, Dominik; Sarac, Mustafa
Abstract: Open rib shear connectors are increasingly used as shear connectors and anchors between concrete and steel members of composite structures. In many cases, the rib connectors are subjected to combined shear and tension forces. However, until now, the structural response and interaction behavior of rib shear connectors exposed to tension and shear has not been analyzed. The current design guidelines do not provide a recommendation for computing the strength of rib shear connectors (traditionally used as shear connectors) under combined tension and shear. Therefore, the present paper presents systematic studies on the interaction behaviour of puzzle-shaped rib shear connectors, also called composite dowels. Based on tests results gained in a novel test setup and FE-simulations, the interaction properties of composite dowel rib connectors are analyzed and a model approach for the tension and shear interaction is proposed. Highlights: New experimental setup for testing rib shear connectors under combined shear and tensile loads Development and validation of FE-models for simulation of rib shear connectors with concrete failure Design models for rib shear connectors under pure shear and pure tension loads Model for tensile -shear - interaction of rib shear connectors